Riesgo-país y tasas de descuento para empresas latinoamericanas - Sabal, Jaime (2007)
This paper identifies the Latin American companies for which the beta calculation is possible and consequently their corporate discount rates with an acceptable degree of confidence. The selection is based on companies whose shares are listed with sufficient liquidity in both local stock markets as well as the New York Stock Exchange. At the time of the sample, 88 companies had qualified for the direct beta calculation. The instability of the liquidity indicators and the market dynamics themselves make it necessary to update the analysis often.